Sinergitas Kinerja Guru Akidah Akhlak dan Guru Bimbingan Konseling dalam Penanganan Kenakalan Siswa - Abdul Hamid Ramdani; Fina Surya Anggraini; Muhammad Ridho Kholiq (STIT Al-Quraniyah Manna, 2021)
Student delinquency is an act or deviant behavior carried out by students in violating the rules that have been set. So that it can interfere with the development of students in the teaching and learning process at school. At school, of course, there are many students who have problems, whether it's from the light or heavy category. This research is focused on what are the forms of student delinquency and the synergy of aqidah morality teachers and counseling guidance teachers in handling student delinquency. The purpose of this study is to find out what forms of student delinquency are as well as to analyze the synergy of the performance of moral teachers and counseling guidance teachers in handling student delinquency. The researcher uses a case study research type with a qualitative approach. The results showed that the forms of student delinquency were: coming late to school, looking untidy, carrying things that were not recommended, taking actions when learning took place, skipping school, smoking, dating, and being disrespectful with teachers. The results of the study also show that the synergy that can be implemented by both of them to deal with students who commit delinquency is through learning and habituation, coaching, ramadan boarding schools, studies Keywords: Performance Synergy, Student Delinquency, Counseling Learning